A new Aceria species (Acari: Eriophyidae) from Spain on Pycnocomon rutifolium (Dipsacaceae) and supplementary descriptions of Aceria eucricotes and A. kuko from Lycium spp. (Solanaceae) - Ripka, Géza; Sánchez, Iňigo (Zootaxa, 2017)
A new species of eriophyoid mite, Aceria pycnocomi sp. nov., associated with Pycnocomon rutifolium (Dipsacaceae), is described and illustrated from Spain. Morphological differences distinguishing this new species from similar Aceria species are discussed. The female, male and nymph of Aceria eucricotes (Nalepa, 1892) and Aceria kuko (Kishida, 1927) are redescribed and illustrated from Spain and Hungary, respectively; both were collected from Lycium spp. (Solanaceae). Morphological differences distinguishing these two species are discussed.